Comparison between sublingual 600 and 800 microgram misoprostol after mifepristone for MTP up to 9 weeks gestation - Thakur, Srishti; Pratap, Charu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The objective of the present study was to compare the efficacy between sublingual 600 and 800 microgram Misoprostol after administration of Mifepristone up to 9 weeks gestation, to compare the incidence of side effects between the two doses. To compare the acceptability between the two doses. Methods: This study is a single-center, randomized study. The study is conducted at Fortis Escorts Hospital and Research Centre, Faridabad, during period of May 2014 to June 2015. 160 Pregnant women with singleton pregnancy up to 9 weeks gestation, visiting OPD of Obstetrics and Gynaecology, who wanted MTP by drug, after taking care of inclusion and exclusion criteria. An informed consent was taken from all the women. Results: In terms of efficacy, both the groups were comparable (p value 0.509). Blood loss was comparable in both the groups (p value 0.147). In terms of side effects, itching and rashes (p value 0.004) and abdominal cramps (p value 0.001) was found to be more in women taking 800ug Misoprostol. Also, need for analgesia (p value 0.001) was found to be more in women taking 800ug Misoprostol. Conclusions: Sublingual Misoprostol is comfortable and easier administration when compared to other routes and it has potential to be developed as a self-administered regimen. 600ug Sublingual Misoprostol is as efficacious as 800ug sublingual Misoprostol with significantly lesser side effects up to 7 weeks of gestation.